Montmorillonite Catalyzed Tandem Synthesis of 1, 1, 3-Trisubstituted-1H-Isochromenes from 3-Phenylisochromenones. (9th August 2022) - Pitchai, Manivel; Teja, Chitrala; Nawaz Khan, Fazlur-Rahman
Abstract: An efficient synthesis of 1, 1, 3-trisubstituted-1H-isochromenes, 3 is reported from isochromen-1-ones, 1 and Grignard Reagents, 2a-h through sequential Grignard reactions/acid-catalyzed cyclization. The cyclization underwent smoothly with montmorillonite K10 catalyst to obtain the 1, 1, 3-trisubstituted-1H-isochromenes in excellent yields.